Development of Flapbook Media on the Ability to Recognize the Consonant Letters “b” and “d” in Children Aged 5–6 Years - Rahmi, Fairuzah Shofiyah; Komalasari, Dewi; Maulidiyah, Eka Cahya; Saroinsong, Wulan Patria (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study was motivated by the lack of learning media and the absence of materials that support early childhood understanding of distinguishing the letters “b” and “d” as a foundation of language education. The research aimed to develop Flapbook media to improve the ability of children aged 5–6 years in recognizing the letters “b” and “d,” as well as to test its validity and effectiveness. The method used was Research and Development (R&D) with the ADDIE model (Analyze, Design, Development, Implement, Evaluate). The subjects were 30 children aged 5–6 years at TK Kemala Bhayangkari 1 Surabaya. Data collection techniques included questionnaires and observation, while data analysis employed the Mann-Whitney test. The Flapbook was designed in A4 size. Validation tests by material and media experts indicated that the Flapbook is feasible for use. The results showed Asymp. Sig (2-tailed) < 0.001 < 0.05, meaning the Flapbook was effective in improving children’s ability to recognize “b” and “d.” Repeated activities supported this improvement, suggesting its integration into early childhood curricula.